(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
Analysis of rural settlements’ regional patterns in RA and the features and regional differences of rural population and settlements distribution, as well as villages’ population numbers were revealed and accomplished. Mountainous relief significantly reduces the populated area of RA and influences the rural settlements’ territorial patterns. Uneven distribution of both total and rural population is typical for RA. The distribution of rural population by the settlements’ population number groups in RA is polarized. In 176 villages with permanent population up to 200 (19% of rural settlements) live 1.5% of the total rural population of RA. In villages with population above 3000 (10.4% of rural settlements) live more than 38% of rural population. 83% of rural population lives in villages with population above 1000 (43.1% of total rural settlements). 15.4% of rural population lives in villages with population between 201–1000 (37.8% of rural settlements). The distribution of rural settlements and population in different elevation zones is caused by historical-geographical, natural-geographical, socio-economic, urbanization, regional, geopolitical and other factors. The rural settlements are distributed between 400–2350 m in RA, but 801–1000 and 1801–2000 m zones are more densely populated. 35% of the total rural population lives in 801–1000 m zone (8.3% of country’s territory) and 16.2% of rural population live in 1801–2000 m zone. There are big differences of rural population and settlements number between elevation zones and also regional differences of average population number of villages. The current geographical patterns of the distribution of rural population and settlements and villages’ population numbers have a significant impact on the economy of RA, as well as on different aspects of development of particular regions and settlements. Implementation of socio-economic development programs at different levels should contribute to reduction of existing polarization rural population distribution in RA.